Evaluation of the efficacy and safety of a new flex‐rigid pleuroscope. (28th September 2020) - Ishii, Satoru; Watanabe, Hiromu; Suzuki, Manabu; Hashimoto, Masao; Iikura, Motoyasu; Izumi, Shinyu; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: Objective: New flex‐rigid pleuroscope enables observations with a maximum angle of curvature of 180 °, allowing visualization of the area near the insertion site of the pleuroscope. And, it improved the image quality and channel inner diameter. The aim of this study was to evaluate the clinical effectiveness and safety of a new flex‐rigid pleuroscope. Methods: A retrospective analysis of patients who were examined with a new flex‐rigid pleuroscope under local anesthesia at our institution was conducted. Pleuroscopy was performed in 33 patients with undiagnosed exudative pleural effusions from December 2016 to March 2019. Results: A total of 33 patients (10 women, 23 men); their median age 74 years (range 24‐90) were investigated. Pleuroscopy showed that 18 had malignant pleural disease (54%), and 15 had benign pleural diseases (46%). The top three most frequent causes of pleural disease were pleural metastases of lung carcinoma (30.3%), pyothorax (15.1%), and malignant pleural mesothelioma (12.1%). In 32 cases (97%), observation at the introducer insertion site was possible. It was not possible in one case due to hard adhesions. The diagnostic rate was 100%, and the complication rate was 6.1%. There were no major complications, and minor complications included mild pain (one case) and minor bleeding (one case) that was stanched spontaneously. Conclusions: The new flex‐rigid pleuroscope is effective and safe for diagnosing pleural effusions. The improved bending angle is likely to minimize the blind area. The new pleuroscopy fiberscope may improve the diagnostic rate.